A Tax Benefit Model for Policy Evaluation in Luxembourg: LuxTaxBen - Nizamul Islam; Lennart Flood (Institute for the Study of Labor (IZA), 2015)
We develop a behavioural micro simulation model (LuxTaxBen) that contains very precise information on income tax rules, as well as eligibility-rules for a number of welfare programs, such as social assistance, housing allowance etc. The model has been built specifically for analysing the Luxembourgish tax-transfer system whereby one can generate disposable income for various combinations of hours of work and welfare. It can be used for calculating accurate (net) household incomes conditional on labour supply while income tax rules and the various welfare benefit-levels are complicated functions of earned and unearned income. The LuxTaxBen is capable to handle almost all parts of the Luxembourg tax and transfer systems. Such a model has a great potential to be used for evaluating the effects of tax-benefit policy reforms and other changes on poverty, inequality, incentives and the governmental budget. It provides the users the opportunity to simulate the new rules in the Luxembourg tax-transfer system. The model consists of a number of modules such as module for child benefit, housing allowance, fees for child care. It is constructed in an integrated way so all the modules can be used together. This means that it is possible to analyses the interaction between the different transfer systems.
Keywords: C8; D31; H24; 330; micro simulation; distributional and behavioural effect; welfare